Resim-iş öğretmenliği anabilim dallarına özel yetenek sınavları ile öğrenci alınırken karşılaşılan sorunlar - Kavuran, Tamer (My University, 2003)
The number of candidates for art teaching departments in Education Faculties increases every year. But most of them apply these programmes to find a job because of unemployement. The selection of candidates has an important place in training qualified art teachers. If there are any problems in special ability exams to select candidates for art teaching programmes in Turkey, they should be solved. With this study, it was aimed to determine the opinions of teachers at art teaching programmes about the problems and solutions of special ability tests for art teaching programmes. According to the data obtained from this study it was found that the teachers faced many problems in special ability tests as well as problems dealing with measurement and evaluation.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Sanat; Eğitim; Özel Yetenek